The effectiveness of Edel varieties cacao leaf extract as an antibacterial against Staphylococcus aureus and Porphyromonas gingivalis: an experimental study - Silvia, Rizka Maya; Viandisa, Chrysmyta Fiola; Prihanti, Ayu Mashartini; Wahyukundari, Melok Aris; Arina, Yuliana Mahdiyah Da'at (Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: Staphylococcus aureus (S. aureus) and Porphyromonas gingivalis (P. gingivalis) are the two main bacteria that cause dental and oral disease. Cacao leaves have been reported to have antibacterial properties. However, the active compounds in cacao leaves vary depending on the age of the leaves and the place where these plants grow. This research aims to analyze the active ingredients and antibacterial effectiveness of the Edel varieties cacao leaves against S. aureus and P. gingivalis. Methods: This is an experimental study. The Cacao leaves from PTPN 12 Plantation Banjarsari Jember were extracted by the maceration technique in concentrations of 25, 50, 75%, and 100%. The phytochemical test was then made using the Thin Layer Chromatography (TLC). The antibacterial activity of Cacao leaf extract against S. aureus ATCC 25923 and P. gingivalis ATCC 33277 was examined using the Disc Diffusion technique on Mueller Hinton Agar (MHA) media. Results: The Cacao leaf extract of the Edel varieties from Jember contained flavonoids, saponins, and tannins but did not contain alkaloids. In all concentrations tested, the Cacao leafmextract of the Edel varieties from Jember showed the inhibition zones of S. aureus and P. gingivalis. The concentration of 100% showed the greatest antibacterial activity (The highest antibacterial activity was observed at a concentration of 100%), which was moderate against S. aureus (10.98 mm ± 0,93) and strong against P. gingivalis (11.54 mm ± 0,41). There was a significant difference among concentrations in both the P.gingivalis and S.aureus bacterial groups (p < 0.001). At the same concentration, there was no significant difference between P. gingivalis and S. aureus (p > 0.001). Conclusion: Cacao leaf extract of the Edel varieties contains flavonoids, saponins and tannins and has antibacterial activity against S. aureus and P. gingivalis.